Association of unsaturated fatty acid intake with risk of all-cause death in patients with osteoarthritis - Tianyang Li; Zhenzhou Tang; Sucheng Li; Weigang Jiang; Minhua Lu (Frontiers in Nutrition)
AimTo investigate the relationship between unsaturated fatty acids (UFAs) intake and the risk of all-cause mortality in osteoarthritis (OA) patients.MethodsThis cohort study included the data of 3,271 participants with OA using data from the National Health and Nutrition Examination Survey (NHANES). Univariate and multivariable weighted Cox regression models were applied to analyze the relationship between UFAs intake and the risk of mortality in patients with OA. Subgroup analysis was used in age, gender, cardiovascular disease (CVD), hypertension, and diabetes. Hazard ratio (HR), and 95% confidence interval (CI) were calculated.ResultsThe median follow-up time was 38.00 (69.00, 104.00) months, with 2,670 participants survived and 601 died. Monounsaturated fatty acids (MUFAs) ≥31.30 was associated with reduced risk of all-cause mortality in OA patients (HR = 0.48, 95% CI: 0.32–0.73). Lowered risk of all-cause mortality in OA patients was observed in patients with octadecenoic acid ≥29.14 (HR = 0.50, 95% CI: 0.34–0.72). Eicosenoic acid of 0.15–0.30 (HR = 0.70, 95% CI: 0.55–0.90) or eicosenoic acid ≥0.30 (HR = 0.62, 95% CI: 0.46–0.84) was related to decreased risk of all-cause mortality in OA patients. Polyunsaturated fatty acids (PUFAs) ≥20.33 was associated with reduced risk of all-cause mortality in OA patients (HR = 0.72, 95% CI: 0.54–0.96). Omega-3 fatty acid ≥1.98 was correlated with decreased risk of all-cause mortality in OA patients (HR = 0.60, 95% CI: 0.45–0.81). Decreased risk of all-cause mortality was found in people with alpha-linolenic acid (ALA) of 1.00–1.83 (HR = 0.75, 95% CI: 0.59–0.96) or ALA ≥1.83 (HR = 0.65, 95% CI: 0.46–0.92) in OA patients. Omega-6 fatty acid ≥18.04 (HR = 0.68, 95% CI: 0.51–0.92) or linoleic acid ≥17.89 (HR = 0.67, 95% CI: 0.50–0.90) were related to decreased risk of all-cause mortality in people with OA.ConclusionTotal MUFAs and PUFAs, octadecenoic acid, eicosenoic acid, omega-3 fatty acid, ALA, omega-6 fatty acid and linoleic acid were correlated with decreased risk of all-cause mortality in OA patients, which might suggest the importance of specific UFAs supplement in OA patients.